IMPLEMENTATION OF STRATEGIC ORGANIZATION CHANGE MANAGEMENT, CLEAN CORPORATE GOVERNANCE, TRANSFORMATIONAL LEADERSHIP IN ELECTRICITY COMPANIES IN INDONESIA - Rio Afrianda; Veithzal Rivai Zainal, Indra Siswanti, Lenny Christina Nawangsari (INTERNATIONAL JOURNAL OF ECONOMIC LITERATURE, 2024)
This study explores the sustainability trends within Indonesian power companies, particularly their shift towards renewable energy mix. Employing a strategic management perspective, this research investigates the impact of strategic organizational change management, clean corporate governance, and transformational leadership on business performance mediated by the core values of the state-owned enterprise AKHLAK (Adaptive, Collaborative, Competent, Harmonious, Loyal, and Trustworthy). The study conducted at PT PLN Nusantara Power, utilizing a non-experimental quantitative approach. The data were analyzed using Structural Equation Modeling (SEM) with LISREL 8.8. The study revealed that 'organizational strategic change management' and 'clean corporate governance and transformational leadership' had positive but non-statistically significant effects on business performance. How- ever, the Core Values AKHLAK played a significant mediating role between these factors and business perfor- mance. This underscores the importance of these values in shaping sustainability outcomes. The study recommends integrating AKHLAK values to enhance the benefits of strategic management, contributing to discussions on sus- tainable practices during Indonesia's renewable energy transition.